Optimization of skeleton structure discrimination standard for SMA-13 mixture based on high-temperature performance - Jinshun Xue; Xiao Chen; Wei Zhao; Yuanyuan Wang (PLoS ONE, 2025)
The stone–on–stone contact-interlocked skeleton structure of stone mastic asphalt (SMA) mixtures is crucial for the effective design of the mixture. However, existing skeleton structure discrimination standard (VCAmix < VCADRC) for SMA mixture gradation design is proven to necessitate calibration. To address this, a method was developed to analyse the influence of structural parameters on the high-temperature performance of SMA-13 mixture. And a skeleton structure discrimination standard for the SMA mixture was proposed and subsequently verified through the high-temperature performance of the SMA-13 mixture. The results indicate that variations in testing methods, compaction efforts, and coarse aggregate breakage lead to discrepancies between the key parameters VCADRC and VCAmix when evaluating the skeleton structure discrimination standard for SMA mixtures. Therefore, a volume method was introduced to the VCAmix expression, calculating it using the volume of the cylindrical specimen compacted by the VTM method. Additionally, the VCAmix < 0.95VCADRC(n=25) is recommended as the skeleton structure discrimination standard for SMA mixture gradation design. Which exhibited more prominent high-temperature performance (8% higher shear strength and 15% greater dynamic stability) than the SMA mixtures designed using VCAmix < VCADRC(n=25) as the skeleton structure discrimination standard.